Lenvatinib Suppresses Angiogenesis through the Inhibition of both the VEGFR and FGFR Signaling Pathways - Kenji Ichikawa; Saori Watanabe Miyano; Yusuke Adachi; Masahiro Matsuki; Kiyoshi Okamoto; Junji Matsui (Global Journal of Cancer Therapy - Peertechz Publications, 2016)
Lenvatinib mesilate (lenvatinib) is an oral multiple-receptor tyrosine kinase inhibitor that selectively inhibits the kinase activities of Vascular Endothelial Growth Factor Receptor (VEGFR) 1-3, Fibroblast Growth Factor Receptor (FGFR) 1-4, Platelet-Derived Growth Factor Receptor (PDGFR) α, KIT, and RET. The VEGFR and FGFR signaling pathways are the master regulators of normal and tumor angiogenesis. Lenvatinib showed significant activity in patients with radioiodine-refractory thyroid cancer in a Phase III study and is used in the United States, the European Union, and Japan. Moreover, based on Phase II study, lenvatinib has been approved in the United States for the treatment of patients with advanced renal cell carcinoma in combination with everolimus. In addition, the efficacy of lenvatinib is being evaluated in other cancers, including hepatocellular carcinoma and endometrial cancer. The purpose of this study was to elucidate the mechanism underlying the clinical activities of lenvatinib by using in vitro and in vivo angiogenesis models.  First, we established an in vitro tube formation system, in which capillary-like structures formed on basement membrane extract in response to pro-angiogenic factors. Lenvatinib suppressed tube formation induced by bFGF alone and by bFGF plus VEGF. Furthermore, plasma levels of VEGF and FGF23, pharmacodynamic biomarkers of inhibition of the VEGFR and FGFR signaling pathways, respectively, were up-regulated after the administration of lenvatinib to mice. By contrast, the administration of another VEGFR inhibitor, sorafenib tosylate (sorafenib), up-regulated plasma levels of VEGF but not FGF23. Finally, lenvatinib suppressed bFGF-driven angiogenesis in Matrigel plug assays at low dosage (3 mg/kg), whereas sorafenib did so only at a higher dose (30 mg/kg). These results indicate that lenvatinib inhibits both VEGFR and FGFR in vitro and in vivo. This combined inhibition of both VEGFR and FGFR may lead significant clinical activities.